P-67INTERNET ADDICTION AND MENTAL HEALTH: A CROSS-SECTIONAL ONLINE SURVEY OF ADULTS IN JAPAN. (September 2014) - Katagami, M.; Inoue, K.
Abstract : Internet Addiction Disorder (IAD) can be broadly conceptualized as an inability to control one's use of the Internet which leads to negative consequences in daily life. In recent years, internet addiction began to be dealt with as mental illness in the world of science by relating to various psychological issues. The aim of this study was to investigate depressive symptoms in adults of addictive internet use, and to assess the effect of the various internet applications use on the IAD severity. A cross-sectional online survey was carried out among participants registered for the opinion poll survey of Osaka City University Graduate School of Medicine, Japan. The questionnaire contained demographic information, the use of various internet applications, Self-rating Depression Scale (SDS), and Japanese version of Internet Addiction Test (JIAT). Of the 310 respondents, the mean age was 40.1 (SD = 12.4). Mean JIAT score was 50.06 (SD = 15.21), and mean SDS score was 40.04 (SD = 6.40). Correlation coefficients of SDS score with JIAT score was 0.212 (P < 0.001). Multiple linear regression analysis showed that JIAT score was associated with hours spent on web browsing (P < 0.001) and online chat (P = 0.033). More research is needed to clarify the issue.